2014
DOI: 10.4081/aiua.2014.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Medical expulsive therapy for distal ureteric stones: tamsulosin versus silodosin

Abstract: Tamsulosin and silodosin are equally effective as MET for distal ureteric stones sized 10 mm or smaller. MET with silodosin is associatd with a lower incidence of side effects related to peripheral vasodilation but an higher incidence of retrograde ejaculation when compared to tamsulosin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 28 publications
10
32
1
Order By: Relevance
“…In that era, our results were similar to those of the studies done by Kumar et al [20] and Imperatore et al [21]. Retrograde ejaculation occurred in both groups with no significant difference, as it was reported in 10 (23.3%) and 5 (12.2%) patients in the silodosin and tamsulosin groups, respectively (p = 0.18), but no patients in any group discontinued the medication.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In that era, our results were similar to those of the studies done by Kumar et al [20] and Imperatore et al [21]. Retrograde ejaculation occurred in both groups with no significant difference, as it was reported in 10 (23.3%) and 5 (12.2%) patients in the silodosin and tamsulosin groups, respectively (p = 0.18), but no patients in any group discontinued the medication.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly Imperatore et al [21] reported a shorter stone expulsion time than ours for both silodosin and tamsulosin groups as it was 7.9 and 7.7 days respectively. Ureterolithiasis causing ureteral colic accounts for up to 2% of the hospital emergency admission [19].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our results are in agreement with those of Gupta et al [12] , who reported stone clearance rates of 82% and 58% for their silodosin and tamsulosin groups, respectively; and also in agreement with those of Kumar et al [13] , who reported stone clearance rates of 83.3% and 64.4% for their silodosin and tamsulosin groups, respectively. However, Imperatore et al [14] reported a nonsignificant difference of stone clearance rates between silodosin (88%) and tamsulosin (84%). While Sur et al [15] reported a stone clearance rate of 52%…”
Section: Discussionmentioning
confidence: 99%
“…(16) Vittorio Imperatore et al, compared for the first time tamsulosin and silodosin in the context of MET for distal ureteric stones. (17) In patients presenting with DUS of 610 mm without the use of MET, the reported spontaneous stone clearance rates are between 35.2% and 61% with mean expulsion times ranging between 9.87 and 24.5 days. (18)(19)(20)(21) Several factors can affect spontaneous stone clearance of DUS including: stone size, site, number and also the presence or absence of ureteric smooth muscle spasm and/or submucosal oedema.…”
Section: Discussionmentioning
confidence: 99%